2018
DOI: 10.1007/s11012-018-0881-8
|View full text |Cite
|
Sign up to set email alerts
|

On vibration mitigation and energy harvesting of a non-ideal system with autoparametric vibration absorber system

Abstract: This paper demonstrates that vibration mitigation and energy harvesting can be achieved simultaneously by using of an electricity-generating from autoparametric vibration absorber system (AVAS) and non-ideal system (NIS). The NIS consists of a simple portal frame excited by a small dc motor with eccentric mass, with limited power supply and located on the top. The AVAS consists of a cantilever beam with tip mass parallel coupled to NIS. A piezoelectric material is considered for energy harvesting installed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 39 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Nonlinear behaviors in portal frames, such as the saturation phenomenon, have been reported due to the dominant quadratic nonlinearities [42]- [48]. Other works also reported nonlinear phenomena due to dominant quadratic nonlinearities in different compound structures [37], [39], and [47]- [49]. These studies demonstrated the importance of proper modeling with analytical and numerical techniques to understand their complex behavior.…”
Section: Introductionmentioning
confidence: 94%
“…Nonlinear behaviors in portal frames, such as the saturation phenomenon, have been reported due to the dominant quadratic nonlinearities [42]- [48]. Other works also reported nonlinear phenomena due to dominant quadratic nonlinearities in different compound structures [37], [39], and [47]- [49]. These studies demonstrated the importance of proper modeling with analytical and numerical techniques to understand their complex behavior.…”
Section: Introductionmentioning
confidence: 94%
“…In recent years, there has been extensive research into matters regarding non-ideal systems [4,19,18,3,9,2,8]. Dynamic systems often exhibit chaotic behavior, which complicates the task of parametric identification in experimental systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, other researchers have placed the absorber parallel to the direction of excitation. The absorber exhibits transverse excitation when the natural frequency of the primary structure is commensurable to the natural frequency of the absorber, commonly in a 2:1 ratio, and quadratic nonlinearities are present [13,14,36,37]. This model has been seen to adequately control a structure while harvesting energy [13] and strong interactions between the primary structure's displacement and the energy harvested [36].…”
Section: Introductionmentioning
confidence: 99%